PENGARUH LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DENGAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING PADA POLITEKNIK KESEHATAN KEMENKES SURAKARTA - Hananto Budi Laksono; Endang Winarsih (JURNAL WIRANOMIKA, 2024)
The purpose of this study was to determine the influence of the work environment and work discipline on performance with work motivation as an intervening variable with a case study at the Surakarta Ministry of Health Polytechnic. The sample in this study was 56 employees. The data analysis method used was using a structural equation model (Structural Equation Modeling). SEM offers the ability for path analysis (Path Analytic). The results of the study showed that there is an influence of the Work Environment and Work Discipline on Employee Motivation. There is an Influence of the Work Environment and Work Discipline on Employee Performance. There is no influence of Work Motivation on the Performance of Employees of the Health Polytechnic of the Ministry of Health of Surakarta. The Influence of the Work Environment on Performance with Motivation as a mediating variable on Employees of the Health Polytechnic of the Ministry of Health of Surakarta has not been proven true. The Influence of Work Discipline on Performance with Motivation as a mediating variable on Employees of the Health Polytechnic of the Ministry of Health of Surakarta has not been proven true. Keyword : work environment, work discipline, employee performance, work motivation